Estilo de vida gamer: cartografia de jogadores casuais de jogos eletrônicos na perspectiva da sociedade de consumo - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The evolution of technology and online gaming has led to the expansion of the gaming industry, causing this market to grow and attract customers worldwide. Thus, a loyal community emerged, creating its own lifestyle from the consumption of products that make up the world of online game players. Based on this, the present research aimed to analyze the gamer consumption in the lifestyle of casual gamers of electronic games. It was used as the main theoretical basis the work Life for Consumption by Zygmunt Bauman (2008), which approaches consumption as the center of social relations, in which the consumer makes use of existential strategies that make him/her the product itself. The method used was cartography, with a qualitative, exploratory approach. For data production, direct observation was made in Instagram profiles of online games and gamers' stores, participant-observation in online games, and interviews with casual gamers. The results indicate that, in general, casual gamers start playing games since childhood and during their trajectory with games they often consume products such as video games, peripherals, action figures and virtual items such as skins for weapons and characters. In the logic of the consumer society, we realize that casual gamers do not consume only fun or entertainment, but a gamer lifestyle fostered by a consumerist existential strategy that demands the constancy of the act of buying to sell themselves in order to belong and stay in the gamer community
Gamer lifestyle: cartography of casual electronic game players from the perspective of consumer society
Keywords: Consumo gamer; Sociedade de consumo; Produtos gamers; Itens virtuais; Virtual items; Gaming products; Consumer society; Gamer consumption; CNPQ::CIENCIAS SOCIAIS APLICADAS